Glycoforms of human prostate-specific membrane antigen (PSMA) in human cells and prostate tissue - Yuan, Wei; Liu, Baoqin; Sanda, Miloslav; Wei, Renhuizi; Benicky, Julius; Novakova, Zora; Barinka, Cyril; Goldman, Radoslav (The Prostate, 2022)
INTRODUCTION: N-glycosylation is a ubiquitous and variable posttranslational modification that regulates physiological functions of secretory and membrane-associated proteins and the dysregulation of glycosylation pathways is often associated with cancer growth and metastasis. Prostate-specific membrane antigen (PSMA) is an established biomarker for prostate cancer imaging and therapy. METHODS: Mass spectrometry was used to analyze the distribution of the site-specific glycoforms of PSMA in insect, human embryonic kidney, and prostate cancer cells, and in prostate tissue upon immunoaffinity enrichment. RESULTS: While recombinant PSMA expressed in insect cells was decorated mainly by paucimannose and high mannose glycans, complex, hybrid, and high mannose glycans were detected in samples from human cells and tissue. We noted an interesting spatial distribution of the glycoforms on the PSMA surface-high mannose glycans were the dominant glycoforms at the N459, N476, and N638 sequons facing the plasma membrane, while the N121, N195, and N336 sites, located at the exposed apical PSMA domain, carried primarily complex glycans. The presence of high mannose glycoforms at the former sequons likely results from the limited access of enzymes of the glycosynthetic pathway required for the synthesis of the complex structures. In line with the limited accessibility of membrane-proximal sites, no glycosylation was observed at the N51 site positioned closest to the membrane. CONCLUSIONS: Our study presents initial descriptive analysis of the glycoforms of PSMA observed in cell lines and in prostate tissue. It will hopefully stimulate further research into PSMA glycoforms in the context of tumor staging, noninvasive detection of prostate tumors, and the impact of glycoforms on physicochemical and enzymatic characteristics of PSMA in a tissue-specific manner.
Keywords: PSMA; antigeny povrchové; glutamátkarboxypeptidasa II; posttranslační úpravy proteinů; NAALADase I; N-glycosylation; buněčné linie; prostata; Prostate; Glycosylation; polysacharidy; lidé; staging nádorů; Protein Processing, Post-Translational; nádory prostaty; glutamate carboxypeptidase II; Prostatic Neoplasms; hmotnostní spektrometrie; Cell Line; Male; nádorové biomarkery; glykosylace; Glutamate Carboxypeptidase II; Mass Spectrometry; folate hydrolase; Biomarkers, Tumor; mužské pohlaví; site-specific glycoform; Antigens, Surface; Polysaccharides; Neoplasm Staging; Humans